State management responsibilities in medical examination and treatment activities - Pham, Thị Hồng Tâm (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2024)
Medical examination and treatment activities play a very important and necessary role in human life. Through medical examination and treatment activities, we will be able to diagnose and treat diseases, thereby helping to maintain and protect human health. However, this is also an activity that carries many hidden risks if it is not performed in a way that ensures compliance with professional requirements and business processes. Therefore, state management of this field is very important and necessary. This not only contributes to improving the efficiency of medical examination and treatment activities, but also minimizes the risks that may arise. Starting from there, the article focuses on analyzing, evaluating and clarifying a number of legal regulations governing the state’s management responsibilities in medical examination and treatment activities, while also pointing out limited issues, inadequacies in regulations and law enforcement on this issue and from there, some recommendations for improvement are made.